The Great Silk road’s culture heritage as a factor of the modern cultures dialogue - Kusbekov, D.K. (Ye.A.Buketov Karaganda State University Publ., 2018)
The article deals with the problems of theoretical and practical development of the cultural heritage of the Great Silk Road. Interest in this cultural and historical phenomenon is due to the fact that the peoples of different countries are trying to understand the sources of their spirituality, their national involvement in world culture. The article gives a philosophical analysis of the main trends of scientific and public interest in the Great Silk Road, the idea of its revival as an important factor in the interaction and dialogue of different cultures. The author notes that the process of globalization is associated with both positive and negative consequences. The author, while fully characterizing the issue raised, points out that integration processes are one side of globalization, and the processes of «national disintegration» that destroys the cultural, political and economic components of the life of society are the reverse side. It is noted the need to counter terrorist and extremist crimes, the basis of which is the manipulation of consciousness as an individual, and society as a whole. The article notes the importance of striving for harmonization of relations, for establishing a dialogue, for reducing conflict as an alternative viable strategy. Theoretically, the problem of interpretation of the national problems in the ethical and normative aspect remains significant and actual in practice. Understanding the key issues of intercultural interaction and finding resources to optimize these aspects is an important issue of the present and the future.
Ұлы Жібек жолының мəдени мұрасы қазіргі мəдени қатынастың факторы ретінде
Культурное наследие Великого Шелкового пути как фактор современного диалога культур
Keywords: culture philosophy; cultural heritage; cultural identity; dialogue of cultures; interethnic communication